Lanreotide in metastatic enteropancreatic neuroendocrine tumors - Caplin, Martyn E; Pavel, Marianne; Ćwikła, Jarosław B; Phan, Alexandria T; Raderer, Markus; Sedláčková, Eva; Cadiot, Guillaume; Wolin, Edward M; Capdevila, Jaume; Wall, Lucy; Rindi, Guido; Langley, Alison; et al. (The New England journal of medicine, 2014)
BACKGROUND: Somatostatin analogues are commonly used to treat symptoms associated with hormone hypersecretion in neuroendocrine tumors; however, data on their antitumor effects are limited. METHODS: We conducted a randomized, double-blind, placebo-controlled, multinational study of the somatostatin analogue lanreotide in patients with advanced, well-differentiated or moderately differentiated, nonfunctioning, somatostatin receptor-positive neuroendocrine tumors of grade 1 or 2 (a tumor proliferation index [on staining for the Ki-67 antigen] of <10%) and documented disease-progression status. The tumors originated in the pancreas, midgut, or hindgut or were of unknown origin. Patients were randomly assigned to receive an extended-release aqueous-gel formulation of lanreotide (Autogel [known in the United States as Depot], Ipsen) at a dose of 120 mg (101 patients) or placebo (103 patients) once every 28 days for 96 weeks. The primary end point was progression-free survival, defined as the time to disease progression (according to the Response Evaluation Criteria in Solid Tumors, version 1.0) or death. Secondary end points included overall survival, quality of life (assessed with the European Organization for Research and Treatment of Cancer questionnaires QLQ-C30 and QLQ-GI.NET21), and safety. RESULTS: Most patients (96%) had no tumor progression in the 3 to 6 months before randomization, and 33% had hepatic tumor volumes greater than 25%. Lanreotide, as compared with placebo, was associated with significantly prolonged progression-free survival (median not reached vs. median of 18.0 months, P<0.001 by the stratified log-rank test; hazard ratio for progression or death, 0.47; 95% confidence interval [CI], 0.30 to 0.73). The estimated rates of progression-free survival at 24 months were 65.1% (95% CI, 54.0 to 74.1) in the lanreotide group and 33.0% (95% CI, 23.0 to 43.3) in the placebo group. The therapeutic effect in predefined subgroups was generally consistent with that in the overall population, with the exception of small subgroups in which confidence intervals were wide. There were no significant between-group differences in quality of life or overall survival. The most common treatment-related adverse event was diarrhea (in 26% of the patients in the lanreotide group and 9% of those in the placebo group). CONCLUSIONS: Lanreotide was associated with significantly prolonged progression-free survival among patients with metastatic enteropancreatic neuroendocrine tumors of grade 1 or 2 (Ki-67 <10%). (Funded by Ipsen; CLARINET ClinicalTrials.gov number, NCT00353496; EudraCT 2005-004904-35.).
Keywords: gastrointestinální nádory; Middle Aged; nádory slinivky břišní; přežití bez známek nemoci; lidé středního věku; mužské pohlaví; cyklické peptidy; Delayed-Action Preparations; dvojitá slepá metoda; Antineoplastic Agents; Double-Blind Method; Humans; senioři; průjem; protinádorové látky; Peptides, Cyclic; neuroendokrinní nádory; somatostatin; lidé; Diarrhea; léky s prodlouženým účinkem; Female; Somatostatin; Disease-Free Survival; Neuroendocrine Tumors; Aged; Pancreatic Neoplasms; ženské pohlaví; Gastrointestinal Neoplasms; Male